Chemical constituents of Belamcanda chinensis (L.) DC - Ha, Le Minh; Kiem, Phan Van; Khripach, Natalya (Vietnam Journal of Chemistry, 2014)
From the ethyl acetate extract of the rhizomes from Belamcanda chinensis (Iridaceae) five compounds irisflorentin (1), tectorigenin (2), iristectorigenin A (3), irigenin (4), and acetovanillone(5) were isolated. Their structures were elucidated by spectroscopic methods. This is first report of 5 from B. chinensis. Keywords: Belamcanda chinensis, Iridaceae, acetovanillone.